Financial Therapy and Planning for Families with Special Needs Children - Mitzi Lauderdale; Sandra J Huston (Journal of Financial Therapy, 2012)
This study examines factors associated with the likelihood of having a plan that includes a special needs trust among families that have disabled minor children. Descriptive analyses indicate that the top two reasons families provide for not having a plan are the inability to save and no perceived need. Among families that do indicate having a plan, most do not include a special needs trust. Multivariate analyses reveal that professional involvement (financial, legal, and mental health professionals) is a key factor to increasing the likelihood of having a plan with a special needs trust. Families that have met with a financial advisor are 23 times more likely, and families who are encouraged to create a plan by a mental health professional are almost three times more likely, to have a plan that includes a special needs trust. Results from this study suggest that financial therapists are uniquely positioned to educate and ensure that appropriate plans are in place to provide for the future of children with special needs.
Keywords: financial planning